Factors associated with covid-19 workplace transmission among government healthcare workers in Kelantan, 2020-2021 - Deraman, Muhammad Naim (2023)
This study aimed to identify proportion of COVID-19 and associated factors of workplace transmission among government HCWs. A cross-sectional study, using secondary data of COVID-19 HCW case from a registry by Unit Kesihatan Pekerjaan dan Alam Sekitar (KPAS) in Jabatan Kesihatan Negeri Kelantan, Malaysia, was analysed using Excel and SPSS version 26. Descriptive analysis and multiple logistic regression were performed to identify factors associated with COVID-19 workplace transmission. A total of 660 HCWs diagnosed as positive for COVID-19 between 1 March 2020 and 31 December 2021. The cases was mainly non workplace transmission (77.1%), with workplace transmission cases contributing only 22.9% of the case. The significant factors associated with workplace transmission were the following: Health Associate Professional group (aOR = 1.66; 95% CI = 1.11, 2.63), hospital facility (aOR = 1.63; 95% CI = 1.08, 2.48), health office facility (aOR = 2.19; 95% CI = 1.12, 4.26), and not vaccinated HCWs (aOR = 1.91; 95% CI = 1.01, 3.62). Further investigation is needed to examine environmental and behavioral factors, as their impact on COVID-19 transmission in the workplace has not been adequately explored. Identifying these factors would aid in the development of effective planning and control measures to prevent the spread of the virus in work settings, particularly in high-risk environments.